Hubungan Kemampuan Awal dan Sikap terhadap MIPA dengan Prestasi Belajar MIPA Mahasiswa Jurusan Pendidikan MIPA - Fuad Abd. Rachman; Hartono Hartono (Universitas Negeri Malang, 2016)
The purpose of this research was to examine correlations between cognitive entry behavior and attitude toward mathematics and science (MIPA), and achievement in mathematics and science. The population of the study was the students of MIPA FKIP-UNSRI. There were 140 subjects sample chosen from the population. The Pearson's Product Moment and Multiple Correlation were applied to analyze the data. The results showed that: there was correlation between cognitive entry behavior and achievement in mathematics and science; there was correlation between attitude toward mathematics and science, and achievement in mathematics and science; achievement in mathematics and science can be predicted from cognitive entry behavior and attitude toward mathematics and science.